The Interplay Between Medication Availability, Service Promptness, and Patient Trust in Pharmaceutical Firms - Osigwe, Princewill Chidi; Ehigiator, Onyinyechi Gift; Bello, Binaebi Gloria; Okolo, Olungwe; Iroegbu, Ikechi Iheanacho (British Journal of Marketing Studies, 2025)
This study examines the influence of medication availability and service promptness on patient trust in pharmaceutical services among patients managing chronic conditions in Port Harcourt, Rivers State, Nigeria. Given their frequent reliance on pharmacies for ongoing treatments, patients with long-term conditions like diabetes and hypertension were chosen to provide insights into service reliability and quality. A sample of 200 patients from the top 10 pharmaceutical firms in Port Harcourt was selected through convenience and purposive sampling methods, with respondents proportionally distributed across firms. Data were collected using a structured questionnaire, adapted from the SERVQUAL model and the Expectancy-Disconfirmation Paradigm (EDP), to measure service promptness, medication availability, and patient trust. A confirmatory factor analysis validated the adapted items, while Cronbach’s alpha demonstrated strong internal consistency (? = 0.929). Multiple regression analysis revealed that medication availability and service promptness significantly impact patient trust, explaining 75% of its variance (R² = 0.75). Findings highlight that consistent medication availability and prompt service are crucial to improving patient trust in healthcare settings. The study recommends implementing automated inventory and real-time response management systems to optimize medication availability and promptness, ensuring service reliability and enhancing trust among chronic-care patients.